PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI EKSTRINSIK TERHADAP KINERJA KARYAWAN PADA PT NIKOMAS GEMILANG-BANTEN - Cindy Erlinda; Siti Aesah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the effect of leadership style and extrinsic motivation on employee performance, both partially and simultaneously, at PT Nikomas Gemilang-Banten. This research uses a quantitative method with the Slovin formula, resulting in 85 respondents. The data analysis techniques include data instrument tests, classical assumption tests, linear regression, correlation coefficient, coefficient of determination, and hypothesis testing. The results show that leadership style has a positive effect on employee performance, with a regression equation of Y = 21.118 + 0.574X1, a correlation value of 0.606 indicating a strong relationship, a determination value of 36.8%, and hypothesis testing results of tcount > ttable (6.948 > 1.988) with a significance level of < 0.05. Extrinsic motivation also has a positive effect on employee performance, shown by the regression equation Y = 22.265 + 0.488X2, a correlation value of 0.683 indicating a strong relationship, a determination value of 46.7%, and hypothesis testing results of tcount > ttable (8.529 > 1.988) with a significance level of < 0.05. Furthermore, leadership style and extrinsic motivation simultaneously have a significant effect on employee performance, as indicated by the multiple linear regression equation Y = 14.805 + 0.356X1 + 0.368X2, a correlation value of 0.762 indicating a very strong relationship, a determination value of 58%, and hypothesis testing results of Fcount > Ftable (56.618 > 2.72) with a significance level of < 0.05.